Use of surface‐guided radiation therapy in combination with IGRT for setup and intrafraction motion monitoring during stereotactic body radiation therapy treatments of the lung and abdomen. Issue 5 (20th March 2020) - Heinzerling, John H.; Hampton, Carnell J.; Robinson, Myra; Bright, Megan; Moeller, Benjamin J; Ruiz, Justin; Prabhu, Roshan; Burri, Stuart H.; Foster, Ryan D.
Abstract: Background and purpose: Multiple techniques can be used to assist with more accurate patient setup and monitoring during Stereotactic body radiation therapy (SBRT) treatment. This study analyzes the accuracy of 3D surface mapping with Surface‐guided radiation therapy (SGRT) in detecting interfraction setup error and intrafraction motion during SBRT treatments of the lung and abdomen. Materials and Methods: Seventy‐one patients with 85 malignant thoracic or abdominal tumors treated with SBRT were analyzed. For initial patient setup, an alternating scheme of kV/kV imaging or SGRT was followed by cone beam computed tomography (CBCT) for more accurate tumor volumetric localization. The CBCT six degree shifts after initial setup with each method were recorded to assess interfraction setup error. Patients were then monitored continuously with SGRT during treatment. If an intrafractional shift in any direction >2 mm for longer than 2 sec was detected by SGRT, then CBCT was repeated and the recorded deltas were compared to those detected by SGRT. Results: Interfractional shifts after SGRT setup and CBCT were small in all directions with mean values of <5 mm and < 0.5 degrees in all directions. Additionally, 25 patients had detected intrafraction motion by SGRT during a total of 34 fractions. This resulted in 25 (73.5%) additional shifts of at least 2 mm on subsequent CBCT. When comparing the average vector detected shift by SGRT to the resulting vector shift on subsequent CBCT, no significant difference was found between the two. Conclusions: Surface‐guided radiation therapy provides initial setup within 5 mm for patients treated with SBRT and can be used in place of skin marks or planar kV imaging prior to CBCT. In addition, continuous monitoring with SGRT during treatment was valuable in detecting potentially clinically meaningful intrafraction motion and was comparable in magnitude to shifts from additional CBCT scans. PTV margin reduction may be feasible for SBRT in the lung and abdomen when using SGRT for continuous patient monitoring during treatment.